The tribe of Quraysh: quran stories for young readers - Nazlee, Shazia (Goodwordkidz New Delhi, India, 2005)
This collection presents captivating tales from the Quran, tailored for children to inspire faith and curiosity. Each story is designed to impart valuable lessons and moral values.